Insight into Acquired Brain Injury Factors for Feeling and Faring Better - Durham, Christine (Springer Singapore, 2018)
This book offers an empowering approach to working with people with an acquired brain injury (ABI) based upon the views and perspectives of people with ABI themselves. Drawing upon Christine Durham's own ABI experience and Paul Ramcharan's engagement in disability research over a quarter of a century, this volume gives voice to 36 participants with ABI, as well as carers and other professionals from both urban and rural areas. This unique perspective provides a long-needed, empathic alternative to the deficit-based model of ABI that dominates medical literature and existing rehabilitation models. In Insight into Acquired Brain Injury, the authors use educational and learning principles together with Durham's extensive archive of experiential data to offer a reframing of the nature and experience of ABI and relevant a set of practical, real-world tools for practitioners. These ready-to-adopt-and-adapt scripts, guided interviews, research checklists, thinking tools and other innovative techniques are designed to engage with people and colleagues about brain injury as a means of supporting them to feel and fare better. With compassion and first-hand awareness, Insight into Acquired Brain Injury provides a much-needed perspective that deepens current understanding and translates the complicated life-worlds of people living with ABI in order to motivate, empower and increase their participation.